UJI TIGA GENOTIPE CABAI MERAH (Capsicum annuum L.) PADA FORMULASI PUPUK DI LAHAN GAMBUT - Arief ' Wibowo; Armaini ' '; Wardati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research aims to obtain the superior genotypes of chili (Capsicum annuum L.) that give respons to fertilizer, able to grow and adapted so well, then produce high quality of yield at peat land. The research was conducted by experiment method. The experiment used Split Plot Design contained 3 times of repetition and 2 times formulation of fertilizer that consisted formulation of fertilizer I (Urea 600 kg/ha, TSP 500 kg/ha, KCl 400 kg/ha, organic fertilizer 10 ton/ha) and formulation of fertilizer II (NPK 700 kg/ha where organic fertilizer 15 ton/ha) as principal plot and 3 genotypes (IPB C-120 x IPB C-5, IPB C-2 x IPB C-120 and IPB C-5 x IPB C-120) as subplot. The variables observed were diameter of stem, high of dichotomous, wide of branches, age of blooming, the diameter, length, and weight of fruit respectively and the weight of fruits per plant. The result showed that superior genotypes and formulation of fertilizer in genotypes 3 (IPB C- 5 x IPB C-120) with the formulation of fertilizer II, it was NPK 700 kg/ha and organic fertilizer 15 ton/ha. Keyword : Genotypes of chili, formulation of fertilizer, peatland.